Pengaruh Aplikasi Ekstrak Limbah Puntung Rokok Terhadap Serangan Hama Pada Pertanaman Edamame di Gunung Kupang, Banjarbaru - Rika Norhasiaty Dewi; Noorkomala Sari; Untung Santoso (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Edamame cultivation in lndonesia has experienced various obstacles in it’s development, the main problem that edamame farmers often face is pest attacks. To overcome this problem, it is necessary to provide vegetable pesticides that do not leave negative residues for the environment or living creatures. One of materials that can be used is cigarette waste which there is tobacco that contains nicotine, phenol and eugenol. This compound is believed to control pests. The aim of this research is to determine the effect of application of cigarette waste extract on the intensity pest attacks and determine the best concentration for controlling edamame plant pests. This research used a Randomized Block Design (RAK) with 5 treatments, each treatment repeated 4 times so that a total of 20 experimental units were obtained. P0 = control, without cigarette waste extract treatment, P1 = 5% concentration, P2 = 10% concentration, P3 = 15% concentration, P4 = 20% concentration. The results of this study show that plants where cigarette waste extract was applied had a very significant effect on the intensity value of edamame pest attacks, while the best concentration for controlling edamame plant pests is cigarette waste extract with a concentration of 20% (P4).